THE INFLUENCE OF ORGANIZATIONAL CULTURE, LEADERSHIP STYLE, AND MOTIVATION ON EMPLOYEE PERFORMANCE - Nesa Awalya Choirunnissa Hamidah; Sri Astuti Pratminingsih; Agus Alamsyah Perwiranegara (Prestise: Jurnal Pengabdian Kepada Masyarakat Bidang Ekonomi dan Bisnis, 2025)
This study analyzes the influence of organizational culture, leadership style, and motivation on employee performance at the Defense Information Bureau, Secretariat General of the Ministry of Defense of the Republic of Indonesia. The research object was selected due to its strategic role in state defense information management, where human resource performance is a crucial factor. The research aims to empirically test the partial and simultaneous effects of these three independent variables on employee performance. This research employs a quantitative method with an explanatory approach. Data were collected through closed-ended questionnaires distributed to 52 permanent employees of the Defense Information Bureau, selected using a purposive sampling technique. Data analysis was conducted using SPSS 25 software, including validity, reliability, classical assumption tests, and multiple linear regression analysis. The results show that, partially, organizational culture and motivation have a positive and significant influence on employee performance, whereas leadership style does not show a significant effect. Simultaneously, the three independent variables collectively have a significant impact on employee performance, with a coefficient of determination (R2) of 41.3%. The main conclusion is that organizational culture and motivation are the dominant factors shaping performance in this environment, making the reinforcement of work values and continuous motivation development strategic recommendations.